Control of Trips Pavispinus in Chili (Capsicum annum L) With Root Extrac of Tuba (Derris elliptica) - Muhammad Riadh Uluputty (Agrologia, 2019)
Chili (Capsicum annnum L.) is one of the horticultural commodities that has economic value. The aim of the research was to determine the effect of root extract of tubal (Derris elliptica) on various concentration levels to control Trips pavispinnus in red chili plants. The treatment tried is three extra concentrations of the tubal root; 10, 20, and 30 g of tubal root / water and one treatment without tubal roots as a control. The treatment was designed using a randomized block design with three replications. Rensposes observed were percentages of Trips pavispinnus mortality. The results showed that the extract of the root of the tuba can control the pest of Trips pavispinnus. The concentration of 10 g / L of water can kill the Trips pavispinnus to 74.42% on the day after application. To be able to prevent the loss of red chilli plants due to a series of  Trips pavispinnus, farmers can take advantage of extracts from the root of the tube, and are an environmentally friendly pest control method.Keywords: Chili, Derris elliptica, Tuba root, Trips pavispinnus